2004
DOI: 10.1016/j.virol.2004.06.045
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence analysis of H5N1 avian influenza A virus isolated from the outbreak among poultry populations in Thailand

Abstract: In this report, the genome of the Thai avian influenza virus A (H5N1); A/Chicken/Nakorn-Pathom/Thailand/CU-K2/04, isolated from the Thai avian influenza A (AI) epidemic during the early of 2004 was sequenced. Phylogenetic analyses were performed in comparison to AI viruses from Hong Kong 1997 outbreaks and other AI (H5N1) isolates reported during 2001-2004. Molecular characterization of the Thai AI (H5N1) HA gene revealed a common characteristic of a highly pathogenic AI (HPAI), a 20-codon deletion in the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…The NA protein of the Danish isolates were characterised by a 20 amino acid deletion at positions 49 to 68 in the stalk region of NA. This deletion has been observed in many recent HP H5N1 isolates [16,22,23] and is suggested to be adaptation for efficient replication in chickens [24]. …”
Section: Resultsmentioning
confidence: 95%
“…The NA protein of the Danish isolates were characterised by a 20 amino acid deletion at positions 49 to 68 in the stalk region of NA. This deletion has been observed in many recent HP H5N1 isolates [16,22,23] and is suggested to be adaptation for efficient replication in chickens [24]. …”
Section: Resultsmentioning
confidence: 95%
“…Results of genomic analysis of H5N1 avian influenza A viruses isolated in Thailand have been reported. 54) The H5N1 virus was also isolated from tigers and leopards in Thailand. 55) Recently, Kuiken et al 56) showed that domestic cats can be experimentally infected with H5N1 virus and suggested that cats may act as an intermediate host between birds and humans.…”
Section: )mentioning
confidence: 99%
“…The disease poses a considerable public health risk. Not only can viruses infect humans directly, causing severe disease with high mortality, 1 but there is also potential for these viruses to acquire the ability to transmit from human to human either by reassortment with other influenza viruses or by mutation and give rise to new pandemic strains 2 . Avian influenza viruses were first detected in Thailand in January 2004, and through 2006, there were 25 persons infected with laboratory‐confirmed influenza A (H5N1) viruses, including 17 deaths, reported to the World Health Organization (WHO) 3 .…”
Section: Introductionmentioning
confidence: 99%